ANALYSIS OF AVAILABILITY OF HIV TESTING FACILITIES FOR PREGNANT WOMEN IN GELUMBANG DISTRICT - Amadea, Wanda; Annisa Rahmawaty; Muhammad Amin Arigo Saci; Muhammad Cholil Munadi (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Early detection of HIV (Human Immunodeficiency Virus) in pregnant women requires facilities and infrastructure that can be used to conduct examinations. This study aims to analyze access to the availability of HIV examination facilities for pregnant women in Gelumbang District. The research design uses a qualitative method with a descriptive approach. Research informants are divided into 2 main informants, 1 key informant, and 1 supporting informant. The accessibility dimension is known that HIV examination services for pregnant women at the Health Center can be carried out during working days and examinations at village midwives can be carried out every day. The availability dimension is known that the availability of the number of rapid test kits at the Gelumbang Health Center is available according to request. The acceptance dimension is known that there is no refusal from pregnant women to undergo HIV examination. The affordability dimension is known that HIV examinations for pregnant women at the Gelumbang Health Center are free of charge. The dimension of adequacy is that the available rapid test tools are sufficient to carry out examinations for all pregnant women in the Gelumbang Health Center working area. The awareness dimension is known that the awareness of pregnant women to independently carry out HIV examinations is still low so that the Gelumbang Health Center makes efforts to increase awareness of pregnant women through counseling and outreach methods. The implementation of HIV examination in the Gelumbang Health Center area has been quite good in terms of accessibility, availability, acceptance, affordability, and adequacy, although there are obstacles in terms of awareness but improvements have been made by the Gelumbang Health Center. All health service facilities are expected to ensure the availability of facilities to carry out HIV examinations for pregnant women to ensure early detection and appropriate intervention.